Climate change and trade: What unilateral or multilateral actions are needed to mitigate emissions embodied in trade flows? - Quirapas, Dan Andre' (Animo Repository, 2021)
The environmental impact of international trade is a concerning issue in the fight against climate change. Consumption-based accounting of greenhouse gas emissions has shown that nearly a quarter of all CO2 emissions are associated with the production of internationally traded goods. As such, trade liberalization—combined with globally fragmented environmental policies—is often associated with emissions leakages and the formation of pollution havens, as trade allows countries to outsource emissions-intensive production to countries with weaker environmental regulations. Literature on this subject has therefore suggested that a globally coordinated policy response is necessary to mitigate the impact of trade on climate change. This study aims to contribute to the existing literature by identifying the type of unilateral or multilateral actions countries can take to mitigate the impact of embodied emissions associated with bilateral trade. Through a gravity model estimating the impact of regulation, domestic carbon intensities, and several other gravity variables, this study is able to provide novel conclusions in the context of the existing literature. Particularly, a unilateral strengthening of environmental regulation by the importing country can contribute climate change mitigation in the best case, and has a statistically insignificant effect in the worst case. This study also finds that multilateral coordination in technological diffusion, and trading agreements can also aid in mitigation efforts.